2013
DOI: 10.1002/pssb.201350138
|View full text |Cite
|
Sign up to set email alerts
|

Long-range crystal-lattice distortion fields of epitaxial Ge-Sb-Te phase-change materials

Abstract: The structural evolution of Ge-Sb-Te-based phase-change material during molecular beam epitaxy growth is investigated. The in situ and ex situ synchrotron-based X-ray scattering results reveal the formation and evolution of defects-induced inhomogeneities during growth. The scattered intensity in the vicinity of various Bragg reflections indicates a specific scattering vector-dependent anisotropy in the diffuse scattering regime. The average local static distortion fields of the defectsinduced inhomogeneities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In order to overcome this limitation and confirm this observation, the flux rate for MBE grown films should be increased. Finally, grazing incidence XRD has been used to study the in-plane lattice constant of GST grown on GaSb(0 0 1) [52]. Figure 6 shows the in-plane lattice constant of GST as a function of layer thickness.…”
Section: (0 0 1)-oriented Substratesmentioning
confidence: 99%
“…In order to overcome this limitation and confirm this observation, the flux rate for MBE grown films should be increased. Finally, grazing incidence XRD has been used to study the in-plane lattice constant of GST grown on GaSb(0 0 1) [52]. Figure 6 shows the in-plane lattice constant of GST as a function of layer thickness.…”
Section: (0 0 1)-oriented Substratesmentioning
confidence: 99%
“…It was subsequently argued that distortions in the crystalline phase may be sufficiently large to locally break the resonant bonding 13,14 generating covalently bonded local configurations. [15][16][17] Local structure studies of the crystalline phase reported to date are additionally complicated by the fact that the studied films are polycrystalline, with atoms at grain boundaries affecting the average structure and properties of the crystalline phase. It was thus highly desirable to grow epitaxial layers of GeTe and GST, which has been successfully achieved over the past several years.…”
mentioning
confidence: 99%
“…More details about the growth of GST by MBE can be found elsewhere. 8,[11][12][13] After the GST deposition, the samples were cooled down to room temperature and transferred to the in-situ magnetron sputtering chamber (base pressure: 5 Â 10 À8 mbar) for capping with W. For the sputtering of the 50 nm thick W contacting layer, an Ar pressure of 4.6 Â 10 À3 mbar, a 155 V DC bias, and RF power of 100 W were used. The resulting growth rate was approximately 8 nm/min.…”
mentioning
confidence: 99%